A day in the life: stories - Hasan, Anjum (Penguin Random House, 2018)
Quixotic retirees in Coorg and young newly-weds trying to eat meat; teenage boys travelling to Benares in the nineteenth century and a retiree with an anger-management problem in the face of an India whose right wing is rising. Fourteen well-crafted stories give us a sense of the daily Indian life of a wide cast of characters. Hasans protagonists are, as always, living in their own heads a lot of the time, often whimsical and vulnerable outliers. Where is their place in the new order, where have they come from and where are they going? Quietly devastating, subtly subversive and wonderfully wry, Hasan is a home-grown talent whose stories are increasingly the good address for authentic Indian fiction.